Photocatalytic degradation of the herbicide imazapyr: do the initial degradation rates correlate with the adsorption kinetics and isotherms?. Issue 4 (20th December 2017) - Atitar, M. Faycal; Bouziani, Asmae; Dillert, Ralf; El Azzouzi, Mohamed; Bahnemann, Detlef W.
Abstract : The Langmuir–Hinshelwood mechanism applies to the photocatalytic degradation of imazapyr only when assuming the occurence of light-induced changes of the photocatalyst surface affecting the adsorption of the probe molecule. Abstract : The objective of this work is to correlate the photocatalytic degradation of the herbicide imazapyr in aqueous suspensions of the commercially available Evonik Aeroxide TiO2 P25 with the dark adsorption phenomena considering both the equilibrium state and the kinetics of adsorption. The results of this study show that the adsorption of imazapyr onto the TiO2 surface is a second-order reaction and satisfies the criteria required by the Langmuir model. The adsorbed amount of imazapyr is found to be high at pH 3 and to decrease with increasing pH. The kinetics of the photocatalytic degradation of imazapyr were analysed taking into account the effect of the pH as well as of the catalyst mass concentration. However, special attention was focussed on the influence of the reactant concentration on the reaction rate. The Langmuir–Hinshelwood model fitting revealed that the apparent adsorption constant obtained under irradiation is significantly larger than the adsorption constant obtained in the dark. The initial reaction rates of the photocatalytic imazapyr degradation were larger than the initial adsorption rates of the probe molecule on the TiO2 surface. It is therefore concluded that the photocatalytic imazapyr degradation does not follow necessarily a Langmuir–Hinshelwood mechanism despite the fact that a rate law having the mathematical form of the Langmuir–Hinshelwood rate law was successfully used to describe the observed dependence of the initial reaction rates on the initial concentrations. A Langmuir–Hinshelwood mechanism for the photocatalytic imazapyr degradation is compatible only with the additional assumption that the rate constant of adsorption increases by irradiation with UV light.